2018
DOI: 10.1002/2016jf004073
|View full text |Cite
|
Sign up to set email alerts
|

Analytic Theory of Equilibrium Fluvial Landscapes: The Integration of Hillslopes and Channels

Abstract: A physically based theory for equilibrium fluvial landscapes undergoing transport‐limited or detachment‐limited erosion is derived from equations for water flow, erosion, and hillslope stability. A scaling analysis of the equations identifies submodels for overland and channelized flows. The channel‐slope boundary (CSB) defines the interface between the two flow environments, marking the bifurcation of stable overland flows into unstable sheet flows and stable channel flows. The characteristics of CSBs are der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…The dynamics of eroding surfaces and related overland flow (including raindrop impact) can be modeled via different approaches, from mechanistic models that consider coupled overland flow and soil erosion (e.g., Hairsine & Rose, 1992a, 1992bNearing et al, 1989) to catchment scale landscape evolution models (LEMs) (e.g., Howard et al, 1994;Perron et al, 2008;Smith, 2018;Willgoose, 1989). LEMs, which predict channel networks at both the catchment and laboratory scales, are relevant to our experimental results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamics of eroding surfaces and related overland flow (including raindrop impact) can be modeled via different approaches, from mechanistic models that consider coupled overland flow and soil erosion (e.g., Hairsine & Rose, 1992a, 1992bNearing et al, 1989) to catchment scale landscape evolution models (LEMs) (e.g., Howard et al, 1994;Perron et al, 2008;Smith, 2018;Willgoose, 1989). LEMs, which predict channel networks at both the catchment and laboratory scales, are relevant to our experimental results.…”
Section: Resultsmentioning
confidence: 99%
“…The consistency between the laboratory results in Figure and and results for catchment networks (e.g., Rodríguez‐Iturbe & Rinaldo, ) points to an underlying governing principle operating at different scales, such as the principle of minimum energy expenditure (Rodríguez‐Iturbe et al, ) that applies at equilibrium conditions for river networks. Similarly, recent work (Smith, ) on equilibrium landscapes showed that overland flows minimized a Lagrangian function of kinetic and potential energies. For both potential (viscosity dominated) and inviscid flows and for fixed boundary conditions, energy dissipation continues monotonically until the steady flow configuration is achieved; that is, energy dissipation is a minimum (Lord, ).…”
Section: Resultsmentioning
confidence: 99%
“…The transition between the unchannelization phase and the initiation phase is then expected to be the time of incipient channelization according to the theory by [3]. The latest experimental, numerical and theoretical studies [12]- [14] show that bifurcation generated by overland flow and seepage erosion should be investigated by process-based approaches. Thus, better flow models and erosion functions may be necessary and important for future research.…”
Section: Discussionmentioning
confidence: 99%
“…A second approach involves deriving solutions to the equations when they are in equilibrium form. This approach is applied in the current paper to a landscape model for which Smith (2018) demonstrated the existence of solutions for both overland and channelized regimes of flow, following a suggestion of Fowler et al (2007) concerning the bistability of the two regimes. An issue with this approach is in selecting appropriate solutions from the many that are consistent with the equations and constraints of a model in equilibrium form.…”
Section: Introductionmentioning
confidence: 98%